The prognostic impact of primary tumour location in patients with stage II and stage III colon cancer receiving adjuvant therapy. A GISCAD analysis from three large randomised trials. (April 2019) - Cascinu, S.; Poli, D.; Zaniboni, A.; Lonardi, S.; Labianca, R.; Sobrero, A.; Rosati, G.; Di Bartolomeo, M.; Scartozzi, M.; Zagonel, V.; Pella, N.; Banzi, M.; et al.
Abstract: Purpose: Because the role of the primary tumour location in the adjuvant setting has not been clearly established in colon cancer, we analysed the clinical outcome according to the primary tumour location from three Italian trials assessing adjuvant therapy in colon cancer. Patients and methods: Overall survival (OS) and disease-free survival (DFS) were assessed globally and in each trial, according to right-sided, transverse and left-sided primary colon cancer. Analysis was planned to provide overall and stage-specific results. Results: Individual data of 5239 patients were included in this analysis. The right-sided tumours were 1540 (29%), tumours originating in the transverse were 815 (16%) and left-sided tumours were 2884 (55%). At the multivariate analysis, DFS findings from the comparison of the right-sided versus left-sided tumours (hazard ratio [HR] = 1.00; 95% confidence interval [CI] = 0.89–1.14) were not statistically associated with clinical outcomes in the overall population. On the contrary, OS findings, from the comparison of the right-sided versus left-sided tumours, were significantly associated with outcomes (HR = 1.20; 95% CI = 1.04–1.39). In stage II patients, there was no difference in terms of DFS and OS among the three different tumour locations, whereas in stage III patients, the left-sided tumours showed an improved prognosis in terms of OS (HR: 1.36 95% CI = 1.14–1.62, p < 0.001). Conclusion: This is the largest analysis demonstrating a prognostic effect of the tumour location on patients with colon cancer receiving adjuvant chemotherapy. Nevertheless, the effect is limited to OS in stage III colon cancer. In stage II tumours, the primary location has a lesser impact. The transverse tumours should be prognostically considered in between the right-sided and left-sided tumours. Highlights: The primary tumour location has a prognostic effect even on patients with colon cancer receiving an adjuvant chemotherapy. The effect is limited to overall survival in stage III colon cancer. The transversum tumours should be prognostically considered between right-sided and left-sided tumours.